Dana Tabbaru’ Sebagai Jaminan Pembiayaan Anggota Baitul Maal Wa Tamwil Dalam Perspektif Hukum Pembiayaan - Frita Azalea Zahra; Eka Setiajatnika; Nurjamil (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2021)
Tabbaru' fund is one of the funds raised in insurance sourced from voluntary funds which is different from premiums on sharia insurance. The purpose of insurance is to mitigate the risks that will be faced by Sharia financial institutions including Baitul Maal Wa Tamwil, one way is to raise Tabbaru's Funds. Dana Tabbaru' has several principles in its implementation, so in its application must be in accordance with the principles and laws of sharia. In practice, Tabbaru' Fund is also applied by other Sharia Financial Institutions such as Baitul Maal Wa Tamwil as a financing guarantee.